PENGARUH DIAMETER ORIFICE TERHADAP KARAKTERISTIK PEREDAM KEJUT MAGNETORHEOLOGICAL PADA KONDISI MEDAN MAGNIT KONSTAN - , FANDI ARMANDA, Ir. Teguh Pudji Purwanto, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nowadays, the development of technology has grown by leaps and bounds. One of them is magnetorheological fluid (MR fluid) which is a smart fluid that its properties can be changed depending on the intensity of the magnetic field influence. Phase changes indicate a change in the viscosity of the magnetic field is affected. The advantages of MR fluid is the dynamic yield strength can be changed when there is the influence of the magnetic field so many applications such as shock absorbers, dampers, etc. In this study will be discussed further on the effect of orifice diameter on the magnetorheological shock absorber with constant magnetic field condition. The characteristics of the MR fluid will be investigated by the force vs displacement graph showing the variation of frequency, stroke, and orifice diameter on the magnetorheological shock absorber. The study was conducted by using MRF-122EG fluid is introduced into the shock absorber that is given electromagnetic solenoid core ridden. The solenoid has a diameter of 1 mm is wound on a shock absorber to reach the 200 loops. Shock absorber is driven by an electric motor that given the variation rate of 0.5 Hz (30 rpm), 0.75 Hz (45 rpm). And 1 Hz (60 rpm) with a stroke of 40 mm and 55 mm. In this study given at constant magnet current at 1,2 A, 2 A, 3 A, and 4 A. Presentation and analysis of the characteristics of the phenomena that occur using the loadcell and sensors that are directly connected to PC. The result is that the higher orifice diameter is given, the higher the damping constant generated. And also the longer stroke is given, the higher the damping constant generated. But the damping constant are not affected by the changes in a given frequency.